Pengaruh E-Commerce, Modal Usaha, Ekspektasi Pendapatan, dan Penggunaan Sistem Informasi Akuntansi Terhadap Pengambilan Keputusan Berwirausaha dengan Self-Efficacy Sebagai Variabel Moderasi - Nur Lailatul Hidayah; Hadiah Fitriyah (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2023)
This study aims to determine the effect of e-commerce, business capital, income expectations, and the use of accounting information systems on entrepreneurial decision making moderated by self-efficacy variables in accounting study program students of Muhammadiyah Sidoarjo University. The population in this study was 761 students. The sample used was 88 respondents' answers, with sampling using the slovin formula and sampling using random sampling. Data collection techniques using questionnaires. The analysis technique uses data analysis in the form of a Partial Least Square (PLS) approach with the SmartPLS software tool verisi 3.2.9. The results of this study show that e-commerce (X1), working capital (X2) and income expectations (X3), self-efficacy (Z) affect entrepreneurial decision making. While the use of accounting information systems (X4) does not affect entrepreneurial decision making. Self-efficacy does not play a role in moderating the relationship between e-commerce variables (X1), working capital (X2), use of accounting information systems (X4) on decision making for entrepreneurship. While self-efficacy plays a role in moderating the relationship between variables of income expectations on entrepreneurial decision making.